Simulation of a seasonal, solar-driven sorption storage heating system. (October 2017) - Engel, Georg; Asenbeck, Sebastian; Köll, Rebekka; Kerskes, Henner; Wagner, Waldemar; van Helden, Wim
Highlights: Solar fraction of 75% in Middle Europe using a compact thermal energy storage. Detailed novel model for the main processes for the sorption thermal energy storage. Validation with realistic-scale demonstration test rig operating several months. Sensitivity analysis and discussion about storage system optimization. Abstract: A detailed simulation setup for a closed solid sorption storage system is developed and validated using extensive experimental data of a demonstration test rig built up in the EU-funded project COMTES. The modular implementation of the sorption process allows to discuss enhanced operation modes like the 'charge boost' in the simulation. The validated model is used to optimize the storage system and to predict its performance for several reference scenarios. As an example, a storage system with 6 m 3 of storage material achieves fractional thermal energy savings in the range of 70–75% for a standard single family house in middle Europe.